2012
DOI: 10.2459/jcm.0b013e32834a3967
|View full text |Cite
|
Sign up to set email alerts
|

The level of serum bilirubin associated with coronary lesion types in patients with coronary artery disease

Abstract: Total serum bilirubin level is an independent risk factor for CAD. It has a strong relationship with coronary artery lesion types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The same result was obtained by Taban Sadeghi et al (2015) who evaluated the relation between serum bilirubin levels with coronary diseases based on angiographic findings, a significant difference was observed between verge total bilirubin levels in two groups: patients with normal angiography & with 3 vessels involved, A reverse relation was observed in this study between total bilirubin levels, number of vessels affected, the severity of stenosis and type of coronary vessel [28]. Wei et al (2012) also showed similar results with a significant inverse correlation between CAD and total bilirubin (n = 1260) in patients who underwent coronary angiography [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The same result was obtained by Taban Sadeghi et al (2015) who evaluated the relation between serum bilirubin levels with coronary diseases based on angiographic findings, a significant difference was observed between verge total bilirubin levels in two groups: patients with normal angiography & with 3 vessels involved, A reverse relation was observed in this study between total bilirubin levels, number of vessels affected, the severity of stenosis and type of coronary vessel [28]. Wei et al (2012) also showed similar results with a significant inverse correlation between CAD and total bilirubin (n = 1260) in patients who underwent coronary angiography [12].…”
Section: Discussionsupporting
confidence: 89%
“…According to Wei et al (2012), a significant inverse correlation between CAD and total bilirubin (n = 1260) in patients who underwent coronary angiography [12].…”
Section: ) Identification Of An Intracoronary Thrombus By Angiographmentioning
confidence: 97%
“…As it is well known that the proportion of HDL and LDL in the TC would be Data are represented as number (%) or mean±SD. As we reported previously, it is associated with coronary artery lesion types [8]. more valuable, it is well accepted that the ratio of LDL and HDL cholesterol is a powerful predictor for cardiovascular diseases [16,17].…”
Section: Discussionmentioning
confidence: 56%
“…Cystatin C (Cys C), however, is a recently discovered biomarker, having a role in the evaluation of renal function [8][9][10]. Uric acid, homocysteine, and so forth are used as indexes for inflammatory diseases as well.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest a possible protective effect of elevated serum bilirubin levels against myocardial ischemia in patients with chronic total coronary occlusion with collaterals limiting infarct size and providing additional blood flow to the ischemic area[29]. Wei et al[30] also showed similar results with a significant inverse correlation between CAD and total bilirubin ( n = 1260) in patients who underwent coronary angiography.…”
Section: Evidence Supporting the Protective Effect Of Bilirubin On Cadmentioning
confidence: 78%